Medical insurance and its impact on tourism: evidence from Vietnam - Wu, Honghua; Van Trung, Ha (Frontiers in Public Health, 2025)
IntroductionHealth security and tourism are increasingly interconnected in shaping sustainable economic development, yet this linkage remains insufficiently examined in emerging economies. This study explores how medical insurance and public health expenditure influence domestic tourism development in Vietnam.MethodsQuarterly time-series data from 2010 to 2023 were analyzed using the Bootstrapped ARDL approach to capture both short-run and long-run dynamics. Robustness checks were conducted through FMOLS and DOLS estimations to validate the consistency of results.ResultsThe findings reveal significant short- and long-run relationships between health insurance coverage and key tourism indicators, including total tourism turnover and average daily expenditure. Medical insurance enhances financial security and psychological assurance, encouraging discretionary travel spending, while public health investment strengthens destination appeal and consumer confidence. Per capita GDP further moderates these effects, amplifying the positive interaction between social protection and tourism outcomes.DiscussionBy establishing a clear link between social protection and tourism economics, the study advances interdisciplinary literature on sustainable tourism. Policy implications highlight the need for integrated health and tourism strategies to foster inclusive, resilient, and sustainable growth. These insights are particularly relevant for Vietnam and other emerging economies seeking to leverage social investment as a driver of tourism development.